Analisis Aktivitas Antioksidan Pada Beras Hitam dan Tepung Beras Hitam (Oryza sativa L.indica) - Muktisari, Ratri Diah; Hartati, Fadjar Kurnia (Food Science and Technology Journal (Foodscitech), 2018)
Black rice and black rice flour is a food product which is very beneficial for the body, because it contains antioxidants. Antioxidant contained in black rice and black rice flour analyzed by examining the antioxidant activity. The purpose of this study is to determine changes to the antioxidant activity of black rice and black rice flour. The research method is using experimental with 2 samples (black rice and black rice flour). In the Data analysis is using independent t test. The results indicate that there are the differences between the antioxidant activity of black rice and black rice flour. It can be concluded that the drying process in the manufacture of black rice flour lowered antioxidant activity in black rice  products.